Al-Quran Based Education Management - Al Firdaus (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2025)
Educational institutions in Indonesia have been established for decades before Indonesia's independence. Educational institutions that have been established still need to be evaluated. Educational management plays an important role in the progress of an educational institution. A quality educational institution can be seen from the management in it. Because if the management is of high quality, then the output of the educational institution is certainly of high quality. In the digital era, educational management is a concern in order to meet the demands of the era that continues to develop. This situation must be adjusted without disappearing existing norms. Educational institutions must continue to make continuous improvements that are not partial in order to form an ideal educational institution in it. Looking at the Elementary School institution, it will be seen which parts must be highlighted in order to make it a strength. Or conversely, it will also be seen which parts have weaknesses. This is related to educational management. Although the word management is very broad and deserves to be re-dissected. This research method uses qualitative context analysis research.